Enforcement, Socioeconomic Diversity, and Tax Filing Compliance in the United States. (13th January 2016) - Alm, James; Clark, Jeremy; Leibel, Kara
Abstract : In this article, we examine the determinants of tax filing compliance in the United States. We use county‐level data on non‐filing rates for the tax year 2000, obtained directly from the Internal Revenue Service. We include explanatory variables identified in the "rational compliance" framework, including an enforcement index against identified non‐filers, the audit rate of filers, and the average penalty rate for both filers and non‐filers. We also examine the role of socioeconomic diversity on tax compliance, testing whether within‐county heterogeneity in household income, language, race, and religion can help explain variation in non‐filing rates. We find that non‐filing is increasing with heterogeneity by race, although not by income or language, and that non‐filing is decreasing with heterogeneity by religious membership. As for enforcement variables, we find that non‐filing rates tend to fall with the enforcement index. Other variables have somewhat mixed results.